Leukocytoclastic Vasculitis in a Patient with Ankylosing Spondylitis - Senol Kobak; Hatice Yilmaz; Ahmet Karaarslan; Murat Yalcin (Case Reports in Rheumatology, 2014)
A 26-year-old male patient presented to our rheumatology clinic with pain, swelling and limitation of movement in his right ankle, and also purpuric skin lesions in the lower extremity pretibial region. He was asked questions, and he said that he had been having chronic low back pain and morning stiffness for the last few years. His physical examination revealed that he had arthritis in his right ankle, purpuric skin lesions in pretibial regions of both legs, and bilateral FABERE/FADIR positivity. The sacroiliac joint imaging and MRI revealed bilateral sacroiliitis findings, and the lateral heel imaging revealed enthesitis. HLA-B27 was positive. Skin biopsy from lower skin lesions was reported to be consistent with leukocytoclastic vasculitis. Based on clinical, laboratory, radiological, and pathological examinations, the patient was diagnosed with ankylosing spondylitis and leukocytoclastic vasculitis. Administration of corticosteroid, salazopyrin, and nonsteroid anti-inflammatory medications was started. Notable clinical and laboratory regression was observed during his checks 3 months later.